A Tribological and Ion Released Research of Ti-Materials for Medical Devices - Paez-Collio, M; Paez-Collio, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The increase in longevity worldwide has intensified the use of different types of prosthe-ses for the human body, such as those used in dental work as well as in hip and knee replacements. Currently, Ti-6Al-4V is widely used as a joint implant due to its good mechanical properties and durability. However, studies have revealed that this alloy can release metal ions or particles harmful to human health. The mechanisms are not well understood yet and may involve wear and/or cor-rosion. Therefore, in this work, commercial pure titanium and a Ti-6Al-4V alloy were investigated before and after being exposed to a simulated biological fluid through tribological tests, surface analysis, and ionic dissolution characterization by ICP-AES. Before exposure, X-ray diffraction and optical microscopy revealed equiaxed α-Ti in both materials and β-Ti in Ti-6Al-4V. Scratch tests exhibited a lower coefficient of friction for Ti-6Al-4V alloy than commercially pure titanium. After exposure, X-ray photoelectron spectroscopy and surface-enhanced Raman spectroscopy results showed an oxide film formed by TiO2, both in commercially pure titanium and in Ti-6Al-4V, and by TiO and Al2O3 associated with the presence of the alloys. Furthermore, inductively coupled plasma atomic emission spectroscopy revealed that aluminum was the main ion released for Ti-6Al-4V, giving negligible values for the other metal ions. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.